Prenatal Yoga and the Reduction of Hypertension Risk in Pregnancy: A Narrative Review - Vina Mustofa; Herdhika Kusumasari; Viska Firdaus (Journal of Research in Midwifery and Healthcare, 2026)
Hypertensive disorders of pregnancy are a major contributor to maternal morbidity and mortality, and growing evidence highlights the need for safe, accessible non-pharmacological strategies to support hemodynamic stability during pregnancy. Prenatal yoga has gained increasing attention as a mind–body intervention that integrates physical postures, breathing techniques, and meditation to enhance both physiological and psychological well-being. This narrative review synthesizes current scientific literature on the mechanisms and outcomes associated with prenatal yoga in reducing the risk of hypertension during pregnancy. Evidence indicates that yoga promotes parasympathetic activation, improves baroreflex sensitivity, increases heart rate variability, and reduces sympathetic overactivity, thereby supporting autonomic balance. Yoga also modulates the hypothalamic–pituitary–adrenal axis by lowering stress hormones, while improving endothelial function through enhanced nitric oxide production and reduced vasoconstriction and inflammation. Clinical findings further demonstrate reductions in systolic and diastolic blood pressure among healthy pregnant women, those at risk for gestational hypertension, and individuals with mild preeclampsia. Psychological benefits, including decreased stress, anxiety, and depressive symptoms, complement these physiological improvements. Collectively, the evidence supports prenatal yoga as a safe, feasible, and effective complementary intervention for promoting cardiovascular stability and reducing hypertension risk in pregnancy. Its integration into antenatal care may offer substantial benefits for maternal health, particularly in low-resource settings.